Immuno-engineered mRNA combined with cell adhesive niche for synergistic modulation of the MSC secretome. (March 2023) - Drzeniek, Norman Michael; Kahwaji, Nourhan; Schlickeiser, Stephan; Reinke, Petra; Geißler, Sven; Volk, Hans-Dieter; Gossen, Manfred
Abstract: In vitro transcribed (IVT-)mRNA has entered center stage for vaccine development due to its immune co-stimulating properties. Given the widely demonstrated safety of IVT-mRNA-based vaccines, we aimed to adopt IVT-mRNA encoding VEGF for secretory phenotype modulation of therapeutic cells. However, we observed that the immunogenicity of IVT-mRNA impairs the endogenous secretion of pro-angiogenic mediators from transfected mesenchymal stromal cells, instead inducing anti-angiogenic chemokines. This inflammatory secretome modulation limits the application potential of unmodified IVT-mRNA for cell therapy manufacturing, pro-angiogenic therapy and regenerative medicine. To uncouple immunogenicity from the protein expression functionality, we immuno-engineered IVT-mRNA with different chemically modified ribonucleotides. 5-Methoxy-uridine-modification of IVT-mRNA rescued the endogenous secretome pattern of transfected cells and prolonged secretion of IVT-mRNA-encoded VEGF. We found that high secretion of IVT-mRNA-encoded protein further depends on optimized cell adhesion. Cell encapsulation in a collagen-hyaluronic acid hydrogel increased secretion of IVT-mRNA-encoded VEGF and augmented the endogenous secretion of supporting pro-angiogenic mediators, such as HGF. Integrating minimally immunogenic mRNA technology with predesigned matrix-derived cues allows for the synergistic combination of multiple dimensions of cell manipulation and opens routes for biomaterial-based delivery of mRNA-engineered cell products. Such multimodal systems could present a more biologically relevant way to therapeutically address complex multifactorial processes such as tissue ischemia, angiogenesis, and regeneration. Graphical abstract: Graphical abstract: Multi-level secretome engineering with immuno-engineered mRNA and biomaterial niche augments the pro-angiogenic paracrine potency of therapeutic cells. Conventional mesenchymal stromal/stem cell (MSC) therapeutics achieve incomplete effects in pro-angiogenic therapy. The pro-angiogenic paracrine effects of MSCs are improved by combining biomaterial-based secretome modulation with immuno-engineered in vitro transcribed (IVT-) mRNA: By immuno-engineering the IVT-mRNA, targeted overexpression of VEGF is uncoupled from the inflammatory secretome shift caused by unmodified mRNA, and instead can be combined with adhesion-mediated upregulation of supporting pro-angiogenic mediators (e.g. HGF). Optimized cell adhesion synergistically increases the secretion of IVT-mRNA encoded VEGF. Orchestration of pro-angiogenic growth factor patterns within the MSC secretome augments the pro-angiogenic potency of the MSC product. Image 1